Data envelopment analysis of efficiency of real estate investment trusts in Singapore. Issue 6 (13th November 2017) - Ahmed, Aminath Amany; Mohamad, Azhar
Abstract : Purpose: In this study, the authors use data envelopment analysis to assess the technical efficiency and performance of real estate investment trusts (REITs) in Singapore, for the years 2009 through 2013. Design/methodology/approach: The authors apply the Malmquist Productivity Index to express the productivity change of the REITs over time. Findings: The authors find that while most REITs have experienced efficiency improvements, there has been little productivity growth at the frontier during the study period. Originality/value: The finding indicates that it is possible to improve the performance of the REITs by further improving technological efficiency because technological regress has been the main reason for the poor productivity growth of the REITs in Singapore.